2016
DOI: 10.1111/dote.12520
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Esophageal Cancer Collaboration: pathologic staging data

Abstract: SUMMARYWe report data-simple descriptions of patient characteristics, cancer categories, and non-riskadjusted survival-for patients with pathologically staged cancer of the esophagus and esophagogastric junction after resection or ablation with no preoperative therapy from the Worldwide Esophageal Cancer Collaboration (WECC). Thirty-three institutions from six continents submitted de-identified data using standard definitions: demographics, comorbidities, clinical cancer categories, and all-cause mortality fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 13 publications
2
54
1
Order By: Relevance
“…Our overall incidence of pulmonary complications and pneumonia in OE was comparable with that of other previous studies (5). The number of harvested lymph nodes was not significantly different (31 vs. 33, P=0.198) between the two groups, satisfying the requirements for the Worldwide Esophageal Cancer Collaboration data (12,13). Lagerson and colleagues suggested that a higher number of harvested lymph nodes provided better survival in esophageal cancer (2).…”
Section: Discussionsupporting
confidence: 85%
“…Our overall incidence of pulmonary complications and pneumonia in OE was comparable with that of other previous studies (5). The number of harvested lymph nodes was not significantly different (31 vs. 33, P=0.198) between the two groups, satisfying the requirements for the Worldwide Esophageal Cancer Collaboration data (12,13). Lagerson and colleagues suggested that a higher number of harvested lymph nodes provided better survival in esophageal cancer (2).…”
Section: Discussionsupporting
confidence: 85%
“…That prognostication based on cTNM differs from that based on pTNM reflects inaccuracies of obtaining cancer facts by current clinical staging modalities. These inaccuracies result in dissimilar stage group composition and survival profiles of cTNM vs. pTNM groups (2,(5)(6)(7).…”
Section: Th Edition Clinical Stagingmentioning
confidence: 99%
“…Clinical staging: prognostication Survival according to cTNM stage groups is "pinched together" compared with pathologic stage groups (2,3,5,6). …”
Section: Clinical Staging: Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to simplify prognostication, the consensus pTNM 5 stage group with equivalent survival to each consensus ypTNM stage group was identified.…”
Section: Introductionmentioning
confidence: 99%